2016
DOI: 10.3177/jnsv.62.341
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Hyperglycemic Effect of a Kudzu (<i>Pueraria lobata</i>) Vine Extract in Ovariectomized Mice

Abstract: Summary Postmenopausal diabetes is exacerbated by estrogen deficiency. Ovariectomized (OVX) animal models can be used to develop strategies for preventing or treating postmenopausal symptoms. We previously found that a diet containing kudzu (Pueraria lobata) vine ethanol extract (PVEE) suppressed weight gain in OVX mice. Therefore, this study further elucidated how PVEE affected OVX mice. Ten-week-old OVX or sham-operated mice were fed diets containing either no PVEE (control) ·d 21 puerarin (daidzein-8-C-gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…Mulberry leaf and Pueraria Lobata are traditional phytomedicines used for DM care in the eastern countries. They have the potentials to inhibit α -glucosidase, stimulate insulin excretion, modulate the intestinal microflora, enhance the glucose utilization in the peripheral tissue, and activate the islet β cells28., 29., 30., 31.. Although the exact pathogenesis of DM is not entirely clear, correlational studies show that some trace elemental nutrients are associated with DM.…”
Section: Introductionmentioning
confidence: 99%
“…Mulberry leaf and Pueraria Lobata are traditional phytomedicines used for DM care in the eastern countries. They have the potentials to inhibit α -glucosidase, stimulate insulin excretion, modulate the intestinal microflora, enhance the glucose utilization in the peripheral tissue, and activate the islet β cells28., 29., 30., 31.. Although the exact pathogenesis of DM is not entirely clear, correlational studies show that some trace elemental nutrients are associated with DM.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there were no signs of uterine hypertrophy in the kudzu vine extractor puerarin-fed mice [11,13,14]. These findings suggest that kudzu vine isoflavones and puerarin improve glucose metabolism without estrogen-like effects on the uterus in OVX mice.…”
Section: Comparison Between Kudzu and Soybean Isoflavonesmentioning
confidence: 48%
“…Therefore, we focused on kudzu vine as an applicable food material. menopausal conditions of OVX mice [11,13,14]. Ten-week-old OVX or sham-operated mice were fed diets without kudzu isoflavones (control) and with 20 mg/kg body weight/day kudzu isoflavones for 8 weeks, 5 mg/kg body weight/day kudzu isoflavones for 24 weeks, 20 mg/kg body weight/day puerarin (daidzein-8-Cglucoside), a major isoflavone present in kudzu vine extracts, for 10 weeks, and 5 mg/kg body weight/day puerarin for 8 weeks.…”
Section: Kudzu Vine As a Food Materials Applicable For Metabolic Disormentioning
confidence: 99%
“…The roots of P. lobata are also used as a component in traditional Chinese medicine to treat chills, colds, fever, and diarrhea. Recent studies have revealed a variety of pharmacological actions of puerarin, such as vasodilatation, cardioprotection, anticancer, and attenuation of menopausal symptoms [29,30]. Orally ingested puerarin is absorbed from the gut into the blood; the oral bioavailability of puerarin has been reported to be approximately 4-7% in animal models [31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%